"Is it because I'm international?": Unpacking experiences of "international instructors" via critical communication pedagogy as aligned with cultural wealth. Issue 2 (3rd April 2022) - Chen, Yea-Wen; Cummins, Molly Wiant; Saindon, Christina E.; Zhang, Dacheng
ABSTRACT: Given the relatively invisible yet growing presence of international academics on U.S. campuses, this study investigates the lived negotiations of "international instructors" across disciplines via critical communication pedagogy (CCP) as aligned with a pedagogy of cultural wealth. We place "international instructors" within quotation marks to challenge a territorial linear logic of the world, and also to facilitate a new space for rethinking academic labors and capitals. Aligned with a pedagogy of cultural wealth, CCP with key commitments to identity, power, culture, and language in the context of pedagogy is an appropriate lens to examine the lived experiences of "international instructors" as outsiders within U.S. academia. We analyzed interviews with 10 self-identified "international instructors" during the 2017-2018 academic year. Our analysis, guided by salient clusters of CCP commitments aligned with unpacking otherness as cultural wealth, identifies three overlapping themes: (a) salient status and wealth of "international instructors" as cocultural members; (b) mundane and repeated communication behaviors reflecting/resisting Eurocentric structures; and (c) distinctive cultural capitals and "international instructors." Working together as an interracial and multinational team, we conclude by discussing pedagogical and practical implications for theorizing otherness as cultural wealth and renewing commitments to internationalization at home in solidarity with "international instructors."